2013
DOI: 10.1371/journal.pone.0063814
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Regulates Glucocorticoid Synthesis in the Adrenal Glands of Trypanosoma cruzi Acutely-Infected Mice. The Role of TNF-R1

Abstract: Adrenal steroidogenesis is under a complex regulation involving extrinsic and intrinsic adrenal factors. TNF-α is an inflammatory cytokine produced in response to tissue injury and several other stimuli. We have previously demonstrated that TNF-R1 knockout (TNF-R1−/−) mice have a dysregulated synthesis of glucocorticoids (GCs) during Trypanosoma cruzi acute infection. Since TNF-α may influence GCs production, not only through the hypothalamus-pituitary axis, but also at the adrenal level, we now investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 34 publications
5
25
1
1
Order By: Relevance
“…Although TNF‐α could contribute to mediate the adrenal response during T. cruzi infection, it persists in TNFR1 and TNFR2 KO mice most likely, because there is a more marked increase in IL‐1 production in these mice, a cytokine known to induce a strong stimulation of the HPA axis . Furthermore, TNF‐α appears to have an inhibitory effect on steroid synthesis by parasite‐infected adrenal cells …”
Section: Overview: Relevance Of Neuroendocrine Host Responses For Thementioning
confidence: 99%
“…Although TNF‐α could contribute to mediate the adrenal response during T. cruzi infection, it persists in TNFR1 and TNFR2 KO mice most likely, because there is a more marked increase in IL‐1 production in these mice, a cytokine known to induce a strong stimulation of the HPA axis . Furthermore, TNF‐α appears to have an inhibitory effect on steroid synthesis by parasite‐infected adrenal cells …”
Section: Overview: Relevance Of Neuroendocrine Host Responses For Thementioning
confidence: 99%
“…Together with the marked elevation in circulating gonadotropins (Tables 2 and 3; Hruska et al 2010;Jeffries et al 2011), which are known to upregulate tumor necrosis factor (Clark and Atwood 2011) and subsequently glucocorticoid synthesis (Villar et al 2013), there is a large growth of the adrenal glands that produce very high concentrations of glucocorticoids which has been postulated to drive tissue degeneration/dysfunction and death of salmon (Carruth et al 2000;Finch 1990;Hruska et al 2010). A similar adrenocortical mechanism impacting immune function has been proposed for the post-mating deaths of males from dasyurid marsupials (Antechinus stuartii and A. favipes) of eastern Australia (Bradley et al 1980;McDonald et al 1981), although in the larger dasyurid Dasyurus hallucatus, there is no evidence of elevated corticosteroid levels during male die-off (Oakwood et al 2001).…”
Section: Ratio Of Sex Steroid/gonadotropin As a Measure Of Dyotic Sigmentioning
confidence: 99%
“…Further studies developed in Tc-infected mice suggested that an ACTH-GC dissociation phenomenon may also occur in this protozoan infection. In fact, findings recorded from a single time point along the course of the acute infection showed that higher circulating levels of GC coexisted with slight ACTH amounts (32,33), raising the view of a GC-driven negative feedback as playing a role in this regard.…”
Section: Introductionmentioning
confidence: 99%